Metabolite compartmentation in Saccharomyces cerevisiae. - Zacharski, C A (1978)
Uninduced cultures of Saccharomyces cerevisiae exhibit high basal levels of allantoinase, allantoicase, and ureidoglycolate hydrolase, the enzymes responsible for degrading allantoin to urea. As a result, these activities increase only 4- to 8-fold upon induction, whereas the urea-degrading enzymes, urea carboxylase and allophanate hydrolase, have very low basal levels and routinely increase 30-fold on induction. Differences in the inducibility of these five enzymes were somewhat surprising because they are all part of the same pathway and have the same inducer, allophanate. Our current studies reconcile these observations. S. cerevisiae normally contained up to 1 mM allantoin sequestered in a cellular organelle, most likely the vacuole. Separation of the large amounts of allantoin and the enzymes that degrade it provide the cell with an efficient nitrogen reserve. On starvation, sequestered allantoin likely becomes accessible to these degradative enzymes. Because they are already present at high levels, the fact that their inducer is considerably removed from the input allantoin is of little consequence. This suggests that at times metabolite compartmentation may play an equal role with enzyme induction in the regulation of allantoin metabolism. Metabolism of arginine, another sequestered metabolite, must be controlled both by induction of arginase and compartmentation because arginine serves both as a reserve nitrogen source and a precursor of protein synthesis. The latter function precludes the existence of high basal levels of arginase.